2021
DOI: 10.2196/33330
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Providers’ Trusted Sources for Information About COVID-19 Vaccines: Mixed Methods Study

Abstract: Background Information and opinions shared by health care providers can affect patient vaccination decisions, but little is known about who health care providers themselves trust for information in the context of new COVID-19 vaccines. Objective The purpose of this study is to investigate which sources of information about COVID-19 vaccines are trusted by health care providers and how they communicate this information to patients. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“… 30 Furthermore, a further reason for doubts arises due to the different methods used by teachers and students in obtaining information. 31 …”
Section: Discussionmentioning
confidence: 99%
“… 30 Furthermore, a further reason for doubts arises due to the different methods used by teachers and students in obtaining information. 31 …”
Section: Discussionmentioning
confidence: 99%
“… 27 Furthermore, the difference in methods used to gain information between students and teachers may be further reason for the difference in hesitancies. 31 At present, the hesitancy of collegial students in different countries (such as Italy, France, and Jordan) is 13.9%–42.0% 32–34 . Bai et al have shown that the students’ hesitancy about COVID-19 vaccination in a Chinese university is 23.7% 19 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, social norms have been identified as the strongest predictors of the intent to be vaccinated against human papillomavirus (HPV) [36,37], as well as a factor that influences parental decisions to vaccinate children [38]. Healthcare workers are repeatedly identified as trusted sources of information which makes them ideal messengers of vaccine-related information both globally and in Ghana [39][40][41], whereas globally fact-framed messages have been found to be less effective [42].…”
Section: Behavioral Insightsmentioning
confidence: 99%
“…It is worth noting that social norms may also have a negative effect on behavior because the perception that "not everyone is doing it" can decrease the intention to act. Therefore, one has to be careful not to send out messages that people are not vaccinating children, as this may lead to unintended effects of vaccine hesitancy [39,40]. The safety frame also requires further consideration as safety was identified as a topic that encourages the uptake of vaccines; it is likely that safety as a message frame has utility.…”
Section: Plos Onementioning
confidence: 99%